Analysis of Commercial and Fiscal Profits, Leverage on Profit Persistence at PT. Mighty True Great - Nurwahyuni, Nurwahyuni; Farid, Faradita; Nurjanna, Anna; Apriani, Indri; Arifin, Muh. Asrullah; Hemeto, Vivianty; Prawitasari, Nungki; Alfarizi, Muhammad Zidane (Universitas Muhammadiyah Makassar, 2024)
This study, titled